DETERMINAN INCOME SMOOTHING DI PERUSAHAAN INFRASTRUKTUR: GCG SEBAGAI PEMODERASI - Tri Ikhsandi, M. Ridho; Heniwati, Elok; Grania Mustika, Ira (Penerbit Lafadz Jaya, 2025)
This study aims to examine the effect of financial leverage, cash holding, company size, and profitability on income smoothing, as well as the role of Good Corporate Governance (GCG) as a moderating variable. The object of the study is infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023, with a total of 75 observations. Data were obtained from annual financial reports and analyzed using binary logistic regression and Moderated Regression Analysis (MRA) with the help of SPSS 30. The results of the study indicate that cash holding has a positive and significant effect, while profitability has a negative and significant effect on income smoothing. Financial leverage and company size do not have a significant effect. Meanwhile, GCG moderates the relationship between cash holding and profitability on income smoothing. GCG strengthens the positive effect of cash holding and weakens the negative effect of profitability on income smoothing but does not moderate the relationship between leverage and company size.